Knowledge and Online Learning through Skill Growth among Higher Education Students - Kumar, R. Manoj; Velmurugan, J. Senthil; kumar, M. Surya (Indian Journal of Information Sources and Services, 2025)
In order to improve college students' competency with technological innovation in various institutions, this research aims to analyse in in-depth understanding of online courses and their effects on skill development. 145 respondents from the colleges were chosen at random to make up the sample. Descriptive statistics and correlation analysis were used to examine the information gathered from the questionnaire. Thus, both government and private college students are included in this poll. The findings demonstrated that students has a tendency to learn online courses as they feel it’s comfortable for them to learn.